AMIODARONE THYROTOXICOSIS IN A PATIENT WITH HYPERTROPHIC CARDIOMYOPATHY - P. Kh. Dzhanashiya; E. V. Avdeeva; N. S. Krylova; S. A. Nikolenko; V. A. Nazarenko (Российский кардиологический журнал, 2009)
A clinical observation of amiodarone thyrotoxicosis in a patient with hypertrophic cardiomyopathy is presented.